STUDI TENTANG PERKEMBANGAN KOGNITIF ANAK USIA PRA-OPERASIONAL YANG INTENSITAS MENGGUNAKAN GADGET DI KELURAHAN KAKASKASEN TIGA - Milinia J. Pongai; Tellma M. Tiwa; Gloridei L. Kapahang (PSIKOPEDIA, 2022)
The research aims to identify and describe the effects of gadget-use intensity on preoperational age children and to find out how gadgets can be used in preoperational age children. The study subjects were married couples (2) who had preoperative children in this study. The child's cognitive development theory is the child's ability to reason and solve problems in the surrounding environment for example, when the child plays with a friend in the surrounding environment must be the child The child will study the situation, the situation surrounding him and the child will later adapt. Gadget Intensity is the degree or size of a situation, condition and activity for the purpose of having fun or breaking away from anxiety, causing pleasure to be repeated and having a certain frequency using a small set of tools that have special applications.It is also used for such games, videos, television, music, youtube as well as interesting applications in the device and is done by the child. This study used a qualitative method using a case study approach. Data collection using interviews and observations. There has been a significant cognitive development of preoperative age children based on the intensity of gadget use. This is evident from three aspects of cognitive development: symbolic thinking, egocentric thinking and intuitive thinking. The essence of using gadgets in this study is about 6 to 7 hours which allows children to start to be able to calculate simple numbers, start to be able to say basic colors both using Indonesian but also English, the child also starts to be able to do simple commands, the child starts to be able to quickly do something, the child also began to be able to imitate and do the will of her own way.